Crowding effect of institutional openness based on the big data algorithm on the efficiency of new energy technology innovation - Cao, Ziying; Qian, Leren (Frontiers in Bioengineering and Biotechnology, 2023)
Under the background of vigorously advocating energy conservation and environmental protection, new energy vehicles (NEV for short here) have been listed as high-tech industries and have received strong support from the government. In the evaluation of innovation efficiency, the article takes human resources, innovation funds, technology acquisition, and environmental support as the main content, and the output includes scientific and technological achievements, economic benefits, and competitiveness. This paper took the “number of new energy project personnel” and “R&D(research and development) personnel hours” as the design indicators to evaluate the investment of innovative talents in enterprises. Firstly, the paper introduced the supporting factors of the innovation environment into the investment of innovation resources, and studied it from four perspectives: human resources, innovation research and development, technology acquisition, and environmental support. In the construction of the innovation output index system, the article believed that the technological innovation (TI for short here) achievements of enterprises were related to the technological capabilities, profits, market competitiveness and other factors of enterprises. Therefore, this paper evaluated it from three aspects: R&D (research and development) achievements, economic benefits obtained and competitive benefits of enterprises. Scientific and technological achievements comprehensively describe the company’s TI output from the three dimensions of patent, literature and market. The indicators of TI efficiency in the past five years were all above 1, and the overall improvement trend of TI was relatively stable. The collaborative innovation system of NEV built in the article would promote the overall development of the NEV industry.